What's New in the Treatment of Migraine?. Issue 3 (September 2019) - Digre, Kathleen B.
Abstract : Background: Migraine is very common. In addition to affecting visual quality of life, migraine can be seen in the neuro-ophthalmology office with regularity. Treatment is critical to assist in the reduction of disability and symptoms. Knowing the evidence-based new treatments is important for every neuro-ophthalmologist. Methods: Using PubMed, and using the term migraine as it related to the terms treatment, evidence-based, calcitonin gene-related peptide (CGRP) inhibitor or antibody, electrical stimulation, vagal nerve stimulation, a literature review was performed. Results: Aside from standard well-described and evidence-based therapies for the acute treatment and prevention of migraine, many new therapies have received FDA approval. In this review, we summarize the contribution of new classes of migraine-specific therapies: CGRP antibodies (erenumab, fremanezumab, galcanezumab, and eptinezumab) for prevention and inhibitors referred to as gepants (ubrogepant and rimegepant) for acute treatment. We also cover newer medications about to be approved, such as lasmitiditan. Devices, including the hand-held vagal nerve stimulator, supraorbital stimulation, transmagnetic stimulation, and remote electrical stimulation, are now approved by the FDA for treatment of migraine. Conclusion: Many new and exciting therapies exist for the treatment of migraine. Keeping up with this rapidly evolving field is important in reducing disability from the common disease of migraine.